The role of gender dysphoria and mother’s parenting style on predicting comorbid mental disorders - Taghizadeh, MohammadEhsan; Oraki, Mohammad; Goshtasbi Asl, Salar (Researcher Bulletin of Medical Sciences, 2019)
Aim: The aim of the current study is to examine the role of parenting style and mental health disorders on individuals with gender dysphoria. Material and Methods: In this study applied research method correlation and research strategies were utilized for data analysis. A total number of 123 patients with gender dysphoria waiting for sex reassignment surgery were recruited from Navidbakhsh clinic in Isfahan and Emergency Social Welfare in Shiraz. The study population was patients with gender dysphoria in Iran (19 males-to-females and 104 female-to-male) were accompanied by their mothers that gender dysphoria them diagnosed by Legal Medicine Organization and they were waiting for sex reassignment surgery from January 2016 to October 2016 have referred to these centers. Results: The data obtained using multiple regressions to standard methods (simultaneous) using SPSS 19 software. Findings from the study showed that between authoritarian parenting style and mental disorders and permissive parenting style and mental disorders there is a negative relationship and between authoritative parenting style and mental disorders there is positive relationship. Conclusions: Each, parenting styles have different relationship with mental disorders, which according to results the best and worst parenting style, authoritarian and authoritative styles are in order.